Birefringent device converts a standard scanning microscope into a STED microscope that also maps molecular orientation - Reuss, Matthias; Engelhardt, Johann; Hell, Stefan (Optics express, 2010)
Stimulated emission depletion (STED) microscopy usually employs a scanning excitation beam that is superimposed by a donut-shaped STED beam for keeping the fluorophores at the periphery of the excitation spot dark. Here, we introduce a simple birefringent device that produces a donut-shaped focal spot with suitable polarization for STED, while leaving the excitation spot virtually intact. The device instantly converts a scanning (confocal) microscope with a co-aligned STED beam into a full-blown STED microscope. The donut can be adapted to reveal, through the resulting fluorescence image, the orientation of fluorophores in the sample, thus directly providing subdiffraction resolution images of molecular orientation.
Gesehen am 15.05.2023